Uncertainty-Aware Robustness Enhancement of Large Language Model Agents for High-Stakes Medical Diagnosis and Treatment Recommendation - Nils Bowers; Siddharth J. Prasad; Fedfrey Waber; Enzo Mills (Bioinformatics Insights and Analytics, 2026)
Large language model (LLM) agents are increasingly being proposed for clinical decision support, yet their deployment in high-stakes medical diagnosis and treatment recommendation remains fraught with unresolved uncertainty challenges. This paper presents a systems-level analysis of uncertainty-aware robustness enhancement for LLM agents operating in clinical environments. We examine the interplay between epistemic and aleatoric uncertainty sources, adversarial vulnerabilities, and the architectural trade-offs inherent in designing agents that can detect, quantify, and appropriately communicate uncertainty. A central argument advanced is that robustness cannot be attained through post-hoc calibration or prompting alone; instead, it requires deeply integrated architectural components such as Bayesian reasoning modules, retrieval-augmented evidence fusion, reinforcement learning with explicit safety constraints, and federated learning frameworks that preserve patient privacy while enabling continuous model improvement. The discussion extends to infrastructure requirements, including latency-accuracy trade-offs in real-time clinical settings, data governance, and the alignment of LLM agent behavior with evolving regulatory standards. We further address fairness considerations, highlighting how uncertainty-aware mechanisms can mitigate disparate performance across demographic subgroups by flagging low-confidence decisions for human review. Long-term sustainability and maintenance of these systems in hospital workflows are examined through the lens of model drift, concept shift, and the need for institutional oversight structures. By synthesizing insights from machine learning, medical informatics, and socio-technical systems theory, the paper offers a roadmap for building trustworthy LLM agents that do not merely generate plausible text but actively manage the limits of their own knowledge in life-critical settings.